2016
DOI: 10.1159/000444209
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genetic Defects Underlying FXII Deficiency in Four Unrelated Chinese Patients

Abstract: Congenital factor XII (FXII) deficiency is a rare autosomal recessive disorder, characterized by a great variability in its clinical manifestations. In this study, we screened for mutations in the F12 gene of 4 unrelated patients with FXII coagulant activity <10% of that of normal human plasma. To investigate the molecular defects in these FXII-deficient patients, we performed FXII mutation screening. By sequencing all coding exons as well as flanking intronic regions of the F12 gene, 6 different mutations, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
(12 reference statements)
1
5
0
Order By: Relevance
“…In addition, expect the proband and his father were heterozygotes 46CT, the other three members all took 46CC genotype, which indicated that the 46CT polymorphism has no significant effect on the reduction of FXII:C in this family. There are no other factors contribute to the activity and antigen reduction of FXII, and the reduced degree of FXII:C and FXII:Ag in the compound heterozygous FXII deficiency is consistent with many previous reports [15,16]. Therefore, we initially believe that the compound heterozygous mutations Glu502Lys and Met527Thr were responsible for the reduction of FXII:C and FXII:Ag.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, expect the proband and his father were heterozygotes 46CT, the other three members all took 46CC genotype, which indicated that the 46CT polymorphism has no significant effect on the reduction of FXII:C in this family. There are no other factors contribute to the activity and antigen reduction of FXII, and the reduced degree of FXII:C and FXII:Ag in the compound heterozygous FXII deficiency is consistent with many previous reports [15,16]. Therefore, we initially believe that the compound heterozygous mutations Glu502Lys and Met527Thr were responsible for the reduction of FXII:C and FXII:Ag.…”
Section: Discussionsupporting
confidence: 91%
“…FXII may be an essential element of thrombosis in vivo [14]. Many reported cases of FXII deficiency have no thrombosis, which is consistent with animal studies [4,10,15,16]. These findings have generated new interest in FXII because it affects thrombosis without affecting hemostasis, so FXII may be the perfect target for the development of new antithrombotic drugs [17].…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…However, Leu500 and Gly542 were conserved in trypsin-like proteins, but Glu502 was not [ 22 ]. The p.Glu502Lys [ 23 ], and p.Gly542Ser FXII gene [ 18 ] mutations have been reported previously.
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…This is the first report of Cys247Tyr, and 252delAsn has been reported. 14 To further prove the adverse effect of Cys247Tyr and 252delAsn, we analyzed their conservatism and the possible effects on the protein. It turns out that in homologous species, Cys247 and Asn252 were highly conserved sites, both of which were considered to be important functional sites of FXII.…”
Section: Discussionmentioning
confidence: 99%